2015
DOI: 10.5152/tjg.2015.4636
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the serum quantitative levels of hepatitis B surface antigen and hepatitis B e antigen in children with chronic hepatitis B

Abstract: Background/Aims: We aimed to investigate the clinical importance of quantitative levels of serum hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg), and to detect their correlation with hepatitis B virus (HBV) DNA load, alanine aminotransferase (ALT) levels, hepatic activity index (HAI) and fibrosis scores. Materials and Methods: A total of 56 HBeAg-positive children with chronic hepatitis B (CHB) were included in the study. Quantification of HBsAg and HBeAg was performed using an automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(33 reference statements)
0
7
0
1
Order By: Relevance
“…Positive correlations have been documented between HBsAg and serum HBV DNA levels in patients with CHB on treatment (11,12). Baseline HBsAg levels have been shown to predict both HBsAg seroclearance (13) and a surrogate marker for monitoring HBV treatment response (14).…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlations have been documented between HBsAg and serum HBV DNA levels in patients with CHB on treatment (11,12). Baseline HBsAg levels have been shown to predict both HBsAg seroclearance (13) and a surrogate marker for monitoring HBV treatment response (14).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these studies, there was no significant relationship between liver histology and qHBsAg levels in only a few studies with small sample size. For instance, Demiroren et al conducted a study on 56 HBeAg positive patients receiving interferon alpha 2b treatment and found no meaningful relationship between qHBsAg level and fibrosis degree (30). Contrary to what was noted in that study, it was demonstrated that qHBsAg levels specifically identified significant fibrosis in treatment-naive HBeAg-positive HBV carriers in another study conducted with a larger patient group (31).…”
mentioning
confidence: 78%
“…In a study carried out by Demiroren et al 56 HBeAg positive children treated with interferon alfa-2b were examined for their pre-treatment and post-treatment qHBsAg levels and a significant difference was observed (30). In another study, Brunetto et al considered the possibility of qHBsAg seroclearance as 30% for patients that show more than 1 log decrease in qHBsAg levels after interferon treatment within 3 years.…”
mentioning
confidence: 99%
“…Ülkemizde yapılan çalışmalarda da, KHB hastalarında HBsAg seviyelerinin HBV DNA ile korelasyon gösterdiği (14)(15)(16) , kantitatif HBsAg ölçümün peg-interferon tedavisinin etkinliğini izlemede HBV DNA ile yer değişebileceği (14) ve inaktif ve aktif taşıyıcıları ayırmada kullanılabileceği (16) bildirmiştir. KHB'li çocuk hastalarda yapılan bir çalışmada da, tedavi sırasında HBsAg, HBeAg, HBV DNA ve ALT seviyelerinin belirgin biçimde düştüğü ve kantitatif HBsAg testlerinin KHB tedavisinin takibinde oldukça önemli role sahip olduğu belirtilmiştir (17) . Başka bir çalışmada ise inaktif taşıyıcılarda kantitatif HBsAg seviyeleri ile HBV DNA arasında herhangi bir ilişki bulunmadığı diğer yandan KHB'li hastalarda kantitatif HBsAg seviyesi ile HBV DNA arasında orta derecede ilişki bulunduğu bildirilmiştir.…”
Section: Discussionunclassified